Body mass index trajectories from ages 1 to 20: Results from two nationally representative canadian longitudinal cohorts. (14th July 2015) - Tu, Andrew W.; Mâsse, Louise C.; Lear, Scott A.; Gotay, Carolyn C.; Richardson, Chris G.
Abstract : Objective: In this study, unique body mass index (BMI) trajectories from ages 1 to 20 years were identified; each trajectory according to socio demographic and family characteristics was described. Methods: Participants came from two national population surveys ( n  = 7, 253; n  = 901) and were aged 1‐6 years at baseline. Children were surveyed biennially over eight waves up to 14‐20 years of age. BMI trajectories by sex and survey cohort were identified by group‐based trajectory modeling. After crossvalidating trajectories between survey cohorts, the characteristics of trajectory membership were assessed by multinomial regression. Results: Four BMI trajectories were found: low, decreasing, medium, and high. The decreasing trajectory was characterized by an overweight or obese childhood followed by a normal‐weight adolescence. The low, medium, and high trajectories were characterized by growth curves culminating, by age 20, to BMI 22.6, 29.3, and 34.9 kg/m 2, respectively, for males and 20.6, 24.5, and 32.0 kg/m 2, respectively, for females. Factors associated with the high trajectory included ethnicity and paternal education (female only), large for gestational age, rural area residence, and maternal smoking. Conclusions: The identification and validation of four major trajectories reflect the heterogeneity in patterns of BMI development from 1 to 20 years.